2014
DOI: 10.1186/1471-2180-14-134
|View full text |Cite
|
Sign up to set email alerts
|

Activation of coagulation and tissue fibrin deposition in experimental influenza in ferrets

Abstract: BackgroundEpidemiological studies relate influenza infection with vascular diseases like myocardial infarction. The hypothesis that influenza infection has procoagulant effects on humans has been investigated by experimental animal models. However, these studies often made use of animal models only susceptible to adapted influenza viruses (mouse adapted influenza strains) or remained inconclusive. Therefore, we decided to study the influence of infection with human influenza virus isolates on coagulation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…An aberrant pro-coagulant response has been previously described to contribute to IAV pathogenesis [15,16]. To determine if an IAV infection in epithelial cells was sufficient to induce a pro-coagulant state in the adjacent endothelial cells, we measured the time to thrombin generation by incubating human plasma with either IAV-or mock-infected co-cultures.…”
Section: Iav Infection Of Epithelial Cells Results In a Pro-coagulantmentioning
confidence: 99%
See 1 more Smart Citation
“…An aberrant pro-coagulant response has been previously described to contribute to IAV pathogenesis [15,16]. To determine if an IAV infection in epithelial cells was sufficient to induce a pro-coagulant state in the adjacent endothelial cells, we measured the time to thrombin generation by incubating human plasma with either IAV-or mock-infected co-cultures.…”
Section: Iav Infection Of Epithelial Cells Results In a Pro-coagulantmentioning
confidence: 99%
“…The inflammatory response to IAV may also result in the upregulation of tissue factor, which can be expressed on both endothelial cells and leukocytes. Increased expression of tissue factor on endothelial cells during IAV infection can result in an aberrant pro-coagulant state, leading to the consumption of coagulation factors, microvascular leak and pulmonary haemorrhage [15][16][17]. Furthermore, a pro-coagulant state induces the release of cytokines such as interleukin (IL)-6 and IL-8 [18], which may further enhance the severity of an IAV-induced cytokine storm and any associated barrier damage.…”
Section: Introductionmentioning
confidence: 99%
“…Goeijenbier et al [43] associated the pro-coagulant state observed in ferrets infected with influenza with the development of infarction. They also observed hemostatic alterations at both vascular and tissue levels during IFV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have partly explained the mechanism of activated coagulation by IAV infection. 48 , 49 IAV activates coagulation by increasing thrombin generation, fibrin deposition and fibrinolysis in C57BL/6 mice. 48 D-dimer (a circulating marker for enhanced coagulation and fibrinolysis) concentrations and von Willebrand factor (vWF) activity are both increased in ferrets after infection with seasonal, pandemic or highly pathogenic avian influenza (HPAI)-H5N1 viruses.…”
Section: Coagulation Disorder Is Associated With Influenza Infectionmentioning
confidence: 99%